Preparation of 10B-enriched nitroimidazole derivative by click reaction as a functional drug for hypoxia-targeting boron-neutron capture therapy - Tatsuya Ozasa; Miu Mizutani; Tatsuya Nishihara; Minoru Suzuki; Kazuhito Tanabe (Results in Chemistry)
We report a novel drug that can be used for the treatment of tumor hypoxic cells by boron neutron capture therapy. We attempted to modify p‑boronophenylalanine, a agent for this therapy in practical use, with a hypoxia-accumulating functional group, 2-nitroimidazole derivative to form p‑boronophenylalanine with nitroimidazole group (BPA-NI). We successfully prepared 10B-enriched BPA-NI by using click chemistry between azide-modified p‑boronophenylalanine and alkyne-modified nitroimidazole in the presence of copper catalysis. This functional molecule showed selective accumulation in hypoxic cells, and therefore showed robust cytotoxic effects toward hypoxic cells upon thermal neutron irradiation.